Dyspepsia in the middle ages: a reference in Giovanni Boccaccio’s Decameron (14th century AD)? - Galassi, Francesco Maria; Spani, Giovanni; Papio, Michael; Toscano, Fabrizio; Artico, Marco; Varotto, Elena (Acta Biomedica Atenei Parmensis, 2023)
.